2007
DOI: 10.1007/s10639-007-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Teaching for blended learning––Research perspectives from on-campus and distance students

Abstract: The concept of blended learning has begun to change the nature of all teaching and learning in higher education. Information and communication technologies have impacted by providing a means of access to digital resources and interactive communication for all courses and the blending of pedagogy and technology has produced a range of approaches to teaching and learning. This paper discusses the research literature and the writers' research, defining what they have concluded are teaching practices that use the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 14 publications
1
36
0
3
Order By: Relevance
“…In another study, learning experience and performance are known to improve when traditional course delivery is integrated with online learning (Stacey & Gerbic, 2007). Such improvement as noted may be an indicator of blended learning effectiveness.…”
Section: Learner Outcomesmentioning
confidence: 90%
“…In another study, learning experience and performance are known to improve when traditional course delivery is integrated with online learning (Stacey & Gerbic, 2007). Such improvement as noted may be an indicator of blended learning effectiveness.…”
Section: Learner Outcomesmentioning
confidence: 90%
“…Stacey and Gerbie (2007) found that struggling learners who were not able to follow the fast-paced class discussion prefer online activities which they perceive are much easier to comprehend. They also found that students were more engaged during online activities as compared to face-to-face class activities, where only the more confident students would participate in the class dialogues (Stacey and Gerbie, 2007). Therefore, using Facebook can truly enhance students' communication and interaction in the target language (Mills, 2009).…”
Section: B Benefits For Efl Studentsmentioning
confidence: 95%
“…Technology innovation has facilitated a number of innovative pedagogies in higher education. Blended learning for example has had a strong impact in both practice (Unger et al, 2013) and Higher Education (Erdem & Kibar, 2014;Lou et al, 2012;Wu et a., 2010) and is particularly suited to university courses where lecture content can be made available online and class time can then be prioritised for active student engagement (Boyinbode et al, 2013;McCarthy, 2010;Stacey & Gerbic, 2007). The blended learning model is based on social constructivism, a student-centred learning theory that stresses the need for collaboration among learners and practitioners.…”
Section: Literature Reviewmentioning
confidence: 99%